Human Factors Testing Sample Size Requirements: Is it Time to Reevaluate?. Issue 1 (June 2021) - Esteve, Savannah; Forkey, Denise; Clark, Shannon
According to the 2016 FDA Human Factors Guidance, Human Factors Validation Testing should include a minimum of 15 test participants from each intended user group for simulated use Human Factors Validation Testing, but there is not specific guidance on sample sizes for studies focused on labeling comprehension. This sample size for labeling comprehension testing has been debated, as some experts suggest that fewer than 15 test participants may be acceptable to achieve similar results. The authors collected data from multiple labeling comprehension studies, to investigate the optimal number of test participants necessary to uncover all use errors specifically when evaluating comprehension and understandability of written instructions, i.e., labeling. While smaller sample sizes may be able to detect most common usability problems, UserWise recommends further investigation of usability study data considering device complexity, user groups, and prior experience level of users to aid the determination of the optimal sample size for adequacy of labeling assessments.